2013
DOI: 10.1021/bm401023h
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection by Silk Cocoons

Abstract: A silk cocoon protects a silkworm during its pupal stage from various threats. We systematically investigated the role of fiber, sericin, and embedded crystals in the UV protection of a silk cocoon. Diffuse reflectance and UV absorbance were measured and free radicals generated during exposure to UV radiation were quantified using photoinduced chemiluminescence (PICL). We identified the response to both UV-A and UV-B radiations by silk materials and found that sericin was primarily responsible for UV-A absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 38 publications
(75 reference statements)
3
56
0
Order By: Relevance
“…It has been reported that similar spectral signatures at ∼28,985 cm1 (∼345 nm) are observed for sericin solutions extracted from A. pernyi silks, with significant variations in UV spectral response of sericin from different silks [51]. The brown pigmentation of certain wild silks has also been hypothesised as resulting from ∼21,740 cm1 (460 nm) absorbing chromophores created through UV photo-oxidation of tyrosine residues, which may play a part in UV protection of the silk cocoon in its pupal stage [51]. …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been reported that similar spectral signatures at ∼28,985 cm1 (∼345 nm) are observed for sericin solutions extracted from A. pernyi silks, with significant variations in UV spectral response of sericin from different silks [51]. The brown pigmentation of certain wild silks has also been hypothesised as resulting from ∼21,740 cm1 (460 nm) absorbing chromophores created through UV photo-oxidation of tyrosine residues, which may play a part in UV protection of the silk cocoon in its pupal stage [51]. …”
Section: Resultsmentioning
confidence: 88%
“…It is typical for proteins in natural bio-materials and is related to ππ* transitions in amino acids that have aromatic rings such as tyrosine, phenylalanine, tryptophan and histidine. Residues of tyrosine in particular have been shown to account for a significant portion of absorption in the 15,800 cm1 (280 nm) region [50,51]. A remnant of sericin in the degummed fibers has a signature with its absorption band at 42,550–46,500 cm1 (215–235 nm) (FWHM) wavelengths [52].…”
Section: Resultsmentioning
confidence: 99%
“…Sericin film increases the proliferation of human skin keratinocytes and fibroblasts, and it accelerates wound healing [49]. Sericin also has antimicrobial, antioxidant, and photo-protective ability from ultraviolet radiation, so it has been effectively used as a dressing material for skin protection [50,51]. Sericin shows potential as a bone tissue engineering scaffolding material.…”
Section: Sericinmentioning
confidence: 99%
“…Ultraviolet radiation (UVR) introduces free radical oxidative stress to organisms and biological materials, resulting in damaged cellular components including DNA and proteins (Tyrrell, 1995;Osaki and Osaki, 2011;Kaur et al, 2013;Matsuhira et al, 2013). Marine and terrestrial organisms have adapted to prevent and cope with such UVR exposure and damage.…”
Section: Introductionmentioning
confidence: 99%